Search for strongly interacting massive particles generating trackless jets in proton–proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Bergauer, T.; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (The European physical journal C)
A search for dark matter in the form of strongly interacting massive particles (SIMPs) using the CMS detector at the LHC is presented. The SIMPs would be produced in pairs that manifest themselves as pairs of jets without tracks. The energy fraction of jets carried by charged particles is used as a key discriminator to suppress efficiently the large multijet background, and the remaining background is estimated directly from data. The search is performed using proton-proton collision data corresponding to an integrated luminosity of 16.1 fb(-1), collected with the CMS detector in 2016. No significant excess of events is observed above the expected background. For the simplified dark matter model under consideration, SIMPs with masses up to 100 GeV are excluded and further sensitivity is explored towards higher masses.